Emprendimiento, una oportunidad de vida para la mujer ecuatoriana - Véliz Valencia, Mercedes Noemi (2023)
The research project aimed to determine entrepreneurship as a life opportunity for Ecuadorian women. We sought to examine the current state of projects and ventures led by women, identifying the difficulties they face in this environment. To achieve this, analysis and interpretation methods will be used to understand each of the processes involved. The main barriers and challenges faced by women entrepreneurs in Ecuador were identified, such as lack of access to financing, gender discrimination and lack of support networks.